2011
DOI: 10.3762/bjoc.7.89
|View full text |Cite
|
Sign up to set email alerts
|

Solvent- and ligand-induced switch of selectivity in gold(I)-catalyzed tandem reactions of 3-propargylindoles

Abstract: SummaryThe selectivity of our previously described gold-catalyzed tandem reaction, 1,2-indole migration followed by aura-iso-Nazarov cyclization, of 3-propargylindoles bearing (hetero)aromatic substituents at both the propargylic and terminal positions, was reversed by the proper choice of the catalyst and the reaction conditions. Thus, 3-(inden-2-yl)indoles, derived from an aura-Nazarov cyclization (instead of an aura-iso-Nazarov cyclization), were obtained in moderate to good yields from a variety of 3-propa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Through these investigations, a combined effect of the electronic/steric properties of the aryl substituent at the propargylic position, auxiliary ligand and solvent was reasoned to the preponderance of Nazarov over the iso-Nazarov selectivity. [204] Gold catalysts in different oxidation state were shown to influence the cyclization of bromoallenylketones 183 to afford regiodivergent halofurans 184 and 185 (Scheme 42). The mechanistic insights of this ligand-controlled selectivity indicate that AuCl 3 favors the formation of 3-bromofuran 184 which is likely to be initiated by the activation of carbonyl group followed by 1,2-Br shift.…”
Section: Alkyl/aryl and Hydride Migrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through these investigations, a combined effect of the electronic/steric properties of the aryl substituent at the propargylic position, auxiliary ligand and solvent was reasoned to the preponderance of Nazarov over the iso-Nazarov selectivity. [204] Gold catalysts in different oxidation state were shown to influence the cyclization of bromoallenylketones 183 to afford regiodivergent halofurans 184 and 185 (Scheme 42). The mechanistic insights of this ligand-controlled selectivity indicate that AuCl 3 favors the formation of 3-bromofuran 184 which is likely to be initiated by the activation of carbonyl group followed by 1,2-Br shift.…”
Section: Alkyl/aryl and Hydride Migrationsmentioning
confidence: 99%
“…Later, an in‐depth investigation regarding the factors influencing the regioselectivity such as reaction conditions, counter‐anion and ligand effects of the Au(I)‐catalyzed selective 1,2‐indole migrations were established. Through these investigations, a combined effect of the electronic/steric properties of the aryl substituent at the propargylic position, auxiliary ligand and solvent was reasoned to the preponderance of Nazarov over the iso‐Nazarov selectivity [204] …”
Section: Alkyl/aryl and Hydride Migrationsmentioning
confidence: 99%
“…In their early works, Echavarren and co-workers reported that C-3 alkynylindole 33 could be transformed either into indoloazocine 34 or into azepino [4,5-b]indole 35, depending on the nature of the employed gold catalyst. [54][55][56][57] Interestingly, for both products the reaction took place through initial coordination of the triple bond of the starting indole (intermediates XIX), followed by intramolecular attack of indole C-3 on XIX to give vinyl gold complexes XX. In both cases the first reaction step is an intramolecular cyclization, leading to spirocyclic intermediates XVII and XVIII, which further evolve to the final products after 1,2-migration of the vinyl group (Scheme 14).…”
Section: Intramolecular Hydroarylation Of Alkynesmentioning
confidence: 99%
“…In a latter report, in 2011, it was showcased that by altering the electronic and steric properties of ligands and reaction conditions (solvent, temperature, and counteranion) it is possible to switch the reactivity of gold(I)-carbene intermediate 95e (generated after a 1,2-indole shift) to follow the Nazarov cyclization pathway and furnish the products 95b. 276 Hence, divergent reaction pathways were accessed from the same substrate to achieve either 1,2-indole shift/Nazarov cyclization product 95b or alternative 1,2-indole shift/iso-Nazarov cyclization product 95c.…”
Section: Ligand-dependent Divergent Gold Catalysis (Ldgc)mentioning
confidence: 99%